Chronic Diseases and Health Care New Trends in Diabetes, Arthritis, Osteoporosis, Fibromyalgia, Low Back Pain, Cardiovascular Disease, and Cancer - Morewitz, Stephen J.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
CHRONIC DISEASES AND HEALTH CARE: New Patterns of Diabetes, Arthritis, Osteoporosis, Fibromyalgia, Low Back Pain, Cardiovascular Disease, and Cancer. Twenty-?ve million Americans are victims of chronic disease, and approximately two-thirds of all deaths each year are due to cardiovascular disease (including stroke), cancer, and diabetes. This book evaluates new trends in epidemiology, health care costs, risk factors, treatment and rehabilitation outcomes, stress and coping strategies, social support, disability, patient education, and self-management for seven prevalent chronic diseases. Case studies from a clinical psychologist’s private practice and the research literature are used to clarify the issues underlying chronic diseases and health care. There are many questions still to be addressed in the ?eld of chronic disease and health care. What is the prevalence of chronic diseases? What are the health care costs associated with these c- ditions? What are the major risk factors and health care disparities that contribute to the development of chronic diseases? How have these risk factors and health care disparities changed over time? What impact do chronic diseases have on disability, quality of life, and health care disparities? How do individuals cope with the stresses of chronic diseases? What are the most effective forms of social support? What are the most effective treatments and v vi PREFACE rehabilitation programs for chronic diseases? How can patient education and self-management activities be improved to help patients and their families better understand and treat their conditions? Chapter One analyzes the latest trends in the epidemiology of.
Chronic Diseases: Epidemiology and Health Care Disparities -- Health Care Costs -- Living with a Chronic Disease -- Diabetes Mellitus -- Rheumatoid Arthritis, Osteoarthritis, Osteoporosis, Fibromyalgia, and Low Back Pain -- Cardiovascular Disease -- Cancer.
Keywords: Public health; Medicine; Public Health; Medicine/Public Health, general